Soil loss estimation using the Revised Universal Soil Loss Equation and geospatial techniques in the Upper Suvarnavathy River Basin, Karnataka, India - Sasi, M; Anil, Sawant Sushant; Deka, Dhanjit (Journal of Degraded and Mining Lands Management, 2025)
Soil erosion occurs gradually when the impact of water or wind detaches and removes soil particles, causing the soil to deteriorate. Because of its adverse effects on biomass and economic production, soil degradation is a worldwide environmental issue. It has a wide-ranging impact on agricultural land and reservoir sedimentation, with disastrous consequences. The Upper Suvarnavathy (Honhole) river basin, Chamarajanagar district, a southern tributary of the Cauvery River of Karnataka, India, was studied to estimate average annual soil loss for a period of 63 years. Remote sensing and GIS approaches combined with the RUSLE model were employed to estimate the soil loss in the study area. To anticipate sheet and rill erosion, the Revised Universal Soil Loss Equation (RUSLE) model considers various factors, such as precipitation (rain) erosivity, soil erodibility, topographic factor, cropping management factor, and support practice factor. The study revealed that the soil erosion in the study area ranges between 0 to 6208.875 t ha?1, and the average has been estimated to be 522.30 t ha?1. This research also determined which RUSLE factor has played a significant role in soil degradation in the study area. The findings will undoubtedly aid in implementing soil management and conservation practices in critical erosion areas in this basin.